Genetic and Hypoxic Control of Dormancy in Barley (Hordeum vulgare) is Linked to Alanine Aminotransferase at the SD1 Locus - Farquharson, Lochlen (Université d'Ottawa / University of Ottawa, 2023)
In malting barley, rapid germination is desirable and linked to end use quality. Modern malting varieties have been bred for low seed dormancy leading to issues with pre-harvest sprouting in wetter growing regions. To maintain malting capacity while minimizing germination on the maternal plant requires in-depth understanding of the genetic regulation of dormancy in malting barley. Currently, the major effect QTLs SD1 and SD2 have been shown to influence dormancy across multiple populations of barley, though the physiological mechanisms involved remain unclear. To search for novel genetic regions that influence primary dormancy, three mapping populations were assessed including two Canadian biparental populations (Synch and Legci) as well as a diversity panel sourced from multiple locations worldwide (ICARDA AM-14). The SD2 locus had a major effect in the Synch population while the SD1 locus had a major effect in the Legci population and neither SD1 nor SD2 were linked to dormancy in the diversity panel. Instead, 14 additional marker trait associations were identified in AM-14 suggesting that investigating a broader range of genetic regulation of dormancy outside of North American varieties may provide solutions to regulate this trait. Additional testing on SD1 revealed that variation at this locus did not affect ABA sensitivity during germination or GA or ABA-regulated gene expression during grain fill. Indeed, lines containing the non-dormant SD1 allele germinate at a similar rate as the dormant SD1 seeds when the glumella was removed from the embryo. This indicated that the effect of the alanine aminotransferase gene underlying the SD1 allele is dependent on physical restriction on the embryo or the hypoxic effects produced by the glumella. Imposing a hypoxic (5% oxygen) environment on exposed embryos revealed an association between non-dormancy at SD1 and reduced sensitivity to the suppressive effects of hypoxia on germination. This suggests that alanine aminotransferase regulates dormancy release during barley germination at least in part through regulation of the seed’s response to hypoxia.
Keywords: Barley; Germination; Alanine Aminotransferase; Dormancy; Pre-harvest sprouting